Public Reporting on Hospital Outcomes in South Africa - Ismail, Fernaaz (My University, 2012)
Hospital performance reports are so new in the South African health care industry that there is no agreement on what aspects of care to measure and no standardised way of capturing, presenting or using the information. This research report determines the challenges that exist in hospital reporting and the way forward in realising how to make hospital quality improvement a part of the business of health care in South Africa. The research method is qualitative research in the interpretive paradigm, using a case study method. Sample groups interviewed represented three key role players in this debate; health care consumers, hospital groups and funders drawn from the case site. The case site, Discovery Health, developed and published South Africa’s first hospital report; the Discovery Hospital Ratings Index. This study found that the widest opportunity in public hospital reporting relates to improving hospital quality and securing better outcomes for patients. It uncovered complex issues that restrict performance reporting (and improvement) efforts; systemic and utilization issues that affect the delivery of care; and that there are certain agreeable conditions in place for dealing with reporting and hospital improvement efforts in South Africa. This research conveys three key messages. The first is simply that the patient comes first. Consequently, patient perspectives of care should ultimately define what is measured and how it is made available. The second is that reporting on hospital performance is only one piece of the puzzle. For improvement efforts to succeed, hospital reports need to guide and be connected to hospital improvement efforts. And finally, deteriorating health care quality and costs are a concern for all of the role players, including health care consumers who were found to be passive participants in both their own care and in broader quality of care debates in South Africa. Each role player can significantly influence hospital quality and cost improvements, but this will require transparency, partnership and accountability
MBA thesis - WBS
Keywords: Hospital performance reports; Healthcare industry